Successful Apprenticeship-to-Work Transitions: On the Long-Term Change in Significance of the German School-Leaving Certificate - Felix Büchel (Institute for the Study of Labor (IZA), 2002)
The quality of labor-market entry achieved by newly qualified apprentices in West Germany is analyzed from 1948 to 1992. A bivariate probit model, using data from the BIBB/IAB employment survey, is applied to estimate simultaneously the quality of the school-toapprenticeship transition and that of the apprenticeship-to-work transition. This shows that school leavers with lower levels of general education are selected into apprenticeships with less favorable employment prospects in all analyzed time periods. However, when controlling for this selection effect, it is only in the most recent period that lower academic achievers are further penalized for the shortcomings in their general education at the apprenticeship-towork transition. Furthermore, the crowding-out of trainees with lower levels of general education can be observed in both the less demanding and the more challenging occupational fields.
Keywords: J44; J24; J21; I21; J62; 330; School-to-work transition; human capital components; apprenticeship system; Berufseinstieg; Lehrstellenmarkt; Humankapital; Bildungsniveau; Überqualifikation; Deutschland; Deutschland